Semi-analytical solution for post-buckling analysis of simply-supported multi-stepped columns. (October 2020) - Ghavanloo, Esmaeal
Abstract: In this paper, semi-analytical solution is developed to predict post-buckling configurations of simply-supported columns consisting of an arbitrary number of segments. Geometric and equilibrium relations of the deformed column are utilized to derive the nonlinear governing equations and the closed-form solution is obtained. Unknown parameters in the proposed solution are determined by using a numerical method. The column is assumed to be an inextensible and the Euler-Bernoulli beam hypotheses are used. The proposed solution is validated by comparing the results obtained with available data in the literature. Furthermore, by using the proposed solution, the post-buckling behaviour of various columns with geometry or material discontinuities is investigated.